2013
DOI: 10.1161/strokeaha.113.001524
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Intracranial Aneurysms in Elderly Patients

Abstract: We assessed the following variables and outcomes: aneurysm rupture status, aneurysm adjunctive treatment technique (balloon-assisted Background and Purpose-Use of endovascular coiling for treatment of ruptured and unruptured intracranial aneurysms (IAs) in the elderly is increasing. We performed a meta-analysis of the literature examining clinical and angiographic outcomes for treatment of IAs in the elderly. Methods-We performed a comprehensive review of the literature from 1995 to 2012, reporting series of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
41
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(44 citation statements)
references
References 33 publications
1
41
0
2
Order By: Relevance
“…9 One meta-analysis of endovascular treatment of intracranial aneurysms in 1511 elderly patients (≥ 65 years old) found that the rate of good neurological outcome without significant disability following unruptured aneurysm coil embolization was 82% at 6-12 months and 91% at 12 months or longer. 11 The rates of combined disability and mortality during long-term follow-up after coil embolization of unruptured aneurysms was between 7% and 15%, similar to our finding of 13%.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…9 One meta-analysis of endovascular treatment of intracranial aneurysms in 1511 elderly patients (≥ 65 years old) found that the rate of good neurological outcome without significant disability following unruptured aneurysm coil embolization was 82% at 6-12 months and 91% at 12 months or longer. 11 The rates of combined disability and mortality during long-term follow-up after coil embolization of unruptured aneurysms was between 7% and 15%, similar to our finding of 13%.…”
Section: Discussionsupporting
confidence: 89%
“…4,11,13 Flow diversion is a more recently developed endovascular technique, and several single-center and multicenter series have reported encouraging early results, especially in the treatment of complex proximal internal carotid artery (ICA) aneurysms.1-3 However, given the relatively small size of these series, the effect of age on periprocedural complication rates and long-term clinical outcomes after flow diversion is difficult to establish. The International Retrospective Study of the Pipeline Embolization Device (IntrePED) is a large multicenter study conducted to assess the incidence of periprocedural complications after Pipeline (Medtronic) embolization of intracranial aneurysms in a "real world" scenario.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Endovascular coil embolization is occasionally preferred in the management of unruptured intracranial aneurysms because it is less invasive than surgical clipping. [5][6][7][8] However, the longterm risk and durability of coil embolization are unknown. 9,10 The frequencies of aneurysm rests or recurrences are higher after coil embolization than that after surgical clipping.…”
mentioning
confidence: 99%
“…A meta-analysis published in 2013 [11] showed high morbidity and mortality (9% and 23% respectively), although this was related more to the severity of the subarachnoid hemorrhage and its complications than to complications of endovascular treatment itself with a 4% aneurysm rupture rate and 5% postoperative ischemic injuries. At 1 year, 66% of patients had recovered well or had only moderate handicap, allowing them to be independent in their activities of daily living.…”
Section: Indicationsmentioning
confidence: 99%